Enantioseparation of Mandelic Acid Enantiomers With Magnetic Nano‐Sorbent Modified by a Chiral Selector. Issue 11 (14th September 2015) - Tarhan, Tuba; Tural, Bilsen; Tural, Servet; Topal, Giray
Abstract In this study, R(+)‐α‐methylbenzylamine‐modified magnetic chiral sorbent was synthesized and assessed as a new enantioselective solid phase sorbent for separation of mandelic acid enantiomers from aqueous solutions. The chemical structures and magnetic properties of the new sorbent were characterized by vibrating sample magnetometry, transmission electron microscopy, Fourier transform infrared spectroscopy, and dynamic light scattering. The effects of different variables such as the initial concentration of racemic mandelic acid, dosage of sorbent, and contact time upon sorption characteristics of mandelic acid enantiomers on magnetic chiral sorbent were investigated. The sorption of mandelic acid enantiomers followed a pseudo‐second‐order reaction and equilibrium experiments were well fitted to a Langmuir isotherm model. The maximum adsorption capacity of racemic mandelic acid on to the magnetic chiral sorbent was found to be 405 mg g−1. The magnetic chiral sorbent has a greater affinity for (S)‐(+)‐mandelic acid compared to (R)‐(−)‐mandelic acid. The optimum resolution was achieved with 10 mL 30 mM of racemic mandelic acid and 110 mg of magnetic chiral sorbent. The best percent enantiomeric excess values (up to 64%) were obtained by use of a chiralpak AD‐H column. Chirality 27:835–842, 2015. © 2015 Wiley Periodicals, Inc.